Preparation and Evaluation of the Cytoprotective Activity of Micelles with DSPE-PEG-C60 as a Carrier Against Doxorubicin-Induced Cytotoxicity - Xu, Beihua; Ding, Zhongpeng; Hu, Ying; Zhang, Ting; Shi, Senlin; Yu, Guangmao; Qi, Xuchen (Frontiers in Pharmacology, 2022)
To deliver doxorubicin (DOX) with enhanced efficacy and safety in vivo, fullerenol-modified micelles were prepared with the amphiphilic polymer DSPE-PEG-C60 as a carrier, which was synthesized by linking C60(OH)22 with DSPE-PEG-NH2. Studies of its particle size, PDI, zeta potential, and encapsulation efficiency were performed. DOX was successfully loaded into the micelles, exhibiting a suitable particle size [97 nm, 211 nm, 260 nm, vector: DOX = 5:1, 10:1; 15:1 (W/W)], a negative zeta potential of around −30 mv, and an acceptable encapsulation efficiency [86.1, 95.4, 97.5%, vector: DOX = 5:1, 10:1; 15:1 (W/W)]. The release behaviors of DOX from DSPE-PEG-C60 micelles were consistent with the DSPE-PEG micelles, and it showed sustained release. There was lower cytotoxicity of DSPE-PEG-C60 micelles on normal cell lines (L02, H9c2, GES-1) than free DOX and DSPE-PEG micelles. We explored the protective role of DSPE-PEG-C60 on doxorubicin-induced cardiomyocyte damage in H9c2 cells, which were evaluated with a reactive oxygen species (ROS) assay kit, JC-1, and an FITC annexin V apoptosis detection kit for cellular oxidative stress, mitochondrial membrane potential, and apoptosis. The results showed that H9c2 cells exposed to DSPE-PEG-C60 micelles displayed decreased intracellular ROS, an increased ratio of red fluorescence (JC-1 aggregates) to green fluorescence (JC-1 monomers), and a lower apoptotic ratio than the control and DSPE-PEG micelle cells. In conclusion, the prepared DOX-loaded DSPE-PEG-C60 micelles have great promise for safe, effective tumor therapy.